2016
DOI: 10.1051/matecconf/20166706099
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Lead with Silica Gel Modified with Polyamidoamine Dendrimer and Thiomalic Acid

Abstract: Abstract.New adsorbents PAMAM-n.0TMSG (n=1,2,3,4) with thiomalic acid as functional group has been prepared based on polyamidoamine dendrimer modified silica gel and characterized with FTIR, SEM and TG. Microcolumn enrichment and measurement of Pb 2+ with graphite furnace atomic absorption spectroscopy (GFAAS) was investigated with PAMAM-n.0TMSG (n=1,2,3,4) as adsorbent. The adsorption conditions were optimized. The increase of grafted generation of PAMAM-n.0TMSG could effectively improved the adsorption perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The spent KCC-1 was analysed using FTIR spectroscopy and was compared with the fresh KCC-1 for identifying the functional groups Silica Gel 14.42 [35] Phenol-formaldehyde/silicon dioxide resin (PFSR) 13.74 [36] Mercapto-modified silica particles 10.42 [37] Anionic layered double hydroxide (LDH) 6.81 [38] that responsible for the adsorption process ( Figure 7). It was observed that the FTIR peaks of the synthesized KCC-1 (3423 cm -1 , 1058 cm -1 , 800 cm -1 , and 450 cm -1 ) were shifted after the adsorption process due to the electrostatic and chemical interaction of functional groups with metal ions [42].…”
Section: Adsorption Performance Of Kcc-1 Synthesized From Rhamentioning
confidence: 99%
“…The spent KCC-1 was analysed using FTIR spectroscopy and was compared with the fresh KCC-1 for identifying the functional groups Silica Gel 14.42 [35] Phenol-formaldehyde/silicon dioxide resin (PFSR) 13.74 [36] Mercapto-modified silica particles 10.42 [37] Anionic layered double hydroxide (LDH) 6.81 [38] that responsible for the adsorption process ( Figure 7). It was observed that the FTIR peaks of the synthesized KCC-1 (3423 cm -1 , 1058 cm -1 , 800 cm -1 , and 450 cm -1 ) were shifted after the adsorption process due to the electrostatic and chemical interaction of functional groups with metal ions [42].…”
Section: Adsorption Performance Of Kcc-1 Synthesized From Rhamentioning
confidence: 99%